PENGARUH KARAKTERISTIK PERUSAHAAN DAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN ANTI KORUPSI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sinta Yulia Permatasari; Andri Prastiwi (Politeknik Ganesha Medan, 2023)
The anti-corruption program is the company's initial defense strategy against corruption. Therefore, the disclosure and transparency of these programs is a commitment in illuminating corruption and improving the ethical behavior of management, employees, partners, agents and other related parties of the company. This study aims to analyze the effect of company characteristics and the board of commissioners on corporate anti-corruption disclosures. The research objects are manufacturing sector companies listed on the IDX in 2020 and 2021. The sampling method is purposive sampling with a sample of 100 companies. Data collection uses research instruments, data analysis is quantitative/statistical in nature with the aim of testing the established hypotheses. Methods of data analysis using SPSS version 25.0. This study found that company size, company age, net profit margin, and board of commissioners have a positive effect on anti-corruption disclosure. Keywords: Anti-corruption Disclosure, Company Characteristics, Board of Commissioners, Manufacturing Companies